Magnetic resonance study of atomic hydrogen stabilized at high densities in solid H2 and D2 matrices - Sheludiakov, S.; Ahokas, J.; Järvinen, J.; Zvezdov, D.; Vainio, O.; Lehtonen, L.; Vasiliev, S.; Mao, S.; Khmelenko, V.V.; Lee, D.M. (Хабаршы. Физика сериясы, 2015)
Hydrogen and deuterium solids at low temperatures represent a special class of quantum crystals, where due to the large zero point oscillations and light mass, the effects of quantum tunnelling play important role. Behaviour of atomic impurities in these crystals attracts special attention due to possibility of reaching collective quantum phenomena related with Bose-Einstein Condensation (BEC) or so-called supersolidbehaviour. This may happen at high enough densities of atomic hydrogen.